Relationship of regular adolescents with their siblings with autism - Laigo, Rowena D. Cepeda (2007)
Siblings commonly share the challenges that the family, having a child with autism, faces. This qualitative and quantitative research was conducted to find out the existing relationship between Filipino regular adolescents and their siblings with autism. Ten participants, all residents of Cavite, were purposively chosen for the study. A researcher-designed intrument and an interview were employed. Families of regular adolescents did not encounter too much difficulties adjusting with the presence of their SWAs and the challenges that came along because the beliefs and values important to them aid in handling each situation with patience and hope. The study is relevant to SPED administrators and teachers in planning interventions for the improvement of their students with autism.
Thesis (M.A. Special Education)--University of the Philippines, Diliman.
Keywords: Austic children -- Family relationships -- Philippines -- Cavite; Special education -- Philippines -- Cavite; Parent and child